Reactivity of a base-stabilized germanium(I) dimer toward group 9 metal(I) chloride and dimanganese decacarbonyl - Muhammad Luthfi Ismail (2020)
The reactivity of the 2-imino-5,6-methylenedioxylphenylgermanium(I) dimer toward group 9 metal(I) chloride and dimanganese decacarbonyl is described. [LGe:]2 (1, L = 2-imino-5,6-methylenedioxylphenyl) underwent a disproportionation reaction with 1.5 equiv of group 9 metal(I) chloride [MCl(cod)]2 (M = Rh, Ir) in toluene to afford a mixture of the group 9 metallogermylene-chlorometal(I) complexes [LGeμ-{M(cod)}2Cl] (M = Rh (2), Ir (4)) and chlorogermylene-chlorometal(I) complexes [L(Cl)GeM(cod)Cl] (M = Rh (3), Ir (5)), respectively. The disproportionation property of 1 is further evidenced by its reaction with 0.5 equiv of Mn2(CO)10 in refluxing toluene to form a mixture of the manganogermylene dimer [(LGe)μ-{Mn(CO)4}]2 (7) and free ligand [LH] (8). Compounds 2-5, 7, and 8 were elucidated by NMR spectroscopy, X-ray crystallography, and DFT calculations, respectively.